Teaching English to Students with Developmental Disabilities: A Study on A School for Disabilities Students in East Lombok - Ismayani, Rahmi; Sahuddin; Arafiq; Amin, Muhammad (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aimed to investigate the teachers’ problems in teaching English to students with developmental disabilities and the factors that cause the problem to arise. This study used a descriptive qualitative method. The subjects of this study were 2 teachers on a school for disabilities students, one teacher was from SMPLB (Sekolah Menengah Pertama Luar Biasa) and one Teacher was from SMALB (Sekolah Menengah Atas Luar Biasa). The data was collected through interviews and observations. The research findings showed that the teachers had problems in teaching English to students with developmental disabilities such as difficulty in find appropriate teaching approach strategies, difficulty in applied sign language, difficulty in explain themselves in English especially orally, and difficulty in managing students. Several factors caused the problems, such as the teachers lack of expertise in teaching English, teachers’ lack skill in classroom management, teachers lack in mastery subject, and teachers lack of skill in general communication with students